The use of indigenous knowledge in beef cattle husbandry in Tshebela Village, Limpopo Province - Mogale, Moneri Sanah (University of Limpopo, 2017)
There is a gap in the literature about the role and relevance of Indigenous Knowledge and beef cattle welfare in many parts of the Limpopo province. This gap is relevant because many marginalised cattle owners use indigenous knowledge in their day to day management of beef cattle. The aim of the study is to investigate the use of IK methods on beef cattle husbandry in Tshebela village in the Capricorn district of the Limpopo province as a contribution to filling the void identified above. The objectives of the study were as follows:  To investigate the IK methods used in beef cattle husbandry in the area of the study;  To assess if beef farmers use IK to identify medicinal plants to cure beef cattle;  To investigate farmers‘ perceptions and attitudes on the use of IKS on beef cattle husbandry in the area of study. A qualitative methodology that was used was primarily phenomenological in design. A purposive sampling technique was used and twenty seven (27) traditional beef farmers, two (2) local herbalists were recruited as participants. Data was collected through focus group discussions, key informant interviews, and observations. An interpretative phenomenological-based analysis was used to surface the role and relevance of indigenous knowledge in beef cattle husbandry. The findings suggest that indigenous knowledge is used by cattle owners alongside modern knowledge and that communal farming posed some challenges to the farmers
Thesis (M. Dev.) -- University of Limpopo, 2017
Keywords: Beef Cattle Husbandry; Beef farming; Indigenous Knowledge; Ethnoscience; Beef cattle -- Breeding -- South Africa; Livestock -- Breeding -- South Africa